Effects of Ice Boom Geometry on Ice Capture Efficiency. - Gooch, Gordon (1996)
An ice boom's geometry is critical to the collectlon and retention of ice in small, fast-moving streams and rivers. Ice booms are designed to quickly form a solid ice cover much earlier than the ice cover would form naturally. Once formed, the ice cover insulates the river, eliminating the production of frazil ice locally. Frazil leads to thick ice deposits, which reduce the river's available flow area and contribute to midwinter and spring flooding. Model experiments, conducted at the Ice Engineering Facility at the Cold Regions Research and Engineering Laboratory, have varied the ice boom geometry to speed up the process of ice cover formation. Model simulations have used floating plastic beads to simulate real ice particles to determine what ice boom design works best. Under controlled laboratory conditions, boom geometry clearly affects the boom's ability to captured more beads. Comparison of field and laboratory tests indicates similar results.